2020
DOI: 10.1186/s13756-020-0678-0
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year resistance trends in pathogens causing healthcare-associated infections; reflection of infection control interventions at a multi-hospital healthcare system in Saudi Arabia, 2007–2016

Abstract: Background: Studying temporal changes in resistant pathogens causing healthcare-associated infections (HAIs) is crucial in improving local antimicrobial and infection control practices. The objective was to describe ten-year trends of resistance in pathogens causing HAIs in a tertiary care setting in Saudi Arabia and to compare such trends with those of US National Health Surveillance Network (NHSN).Methods: Pooled analysis of surveillance data that were prospectively collected between 2007 and 2016 in four ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 38 publications
8
32
4
Order By: Relevance
“…The study finding stated that E. coli and K. pneumonia which exhibited a high resistant rate (34.8 and 38.9%, respectively) to cefotaxime and ceftazidime were classified as extended-spectrum β -lactamase (ESBL) phenotypes. This ESBL prevalence rate was near to the rate reported in the previous studies from Sudan for E. coli and K. pneumonia (28.9% and 34.8%) [ 16 ], and in agreement with other studies reported the growing prevalence of extended-spectrum beta-lactamase (ESBL) producing isolates from Saudi Arabia ranges from 6% up to 38.5% [ 17 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…The study finding stated that E. coli and K. pneumonia which exhibited a high resistant rate (34.8 and 38.9%, respectively) to cefotaxime and ceftazidime were classified as extended-spectrum β -lactamase (ESBL) phenotypes. This ESBL prevalence rate was near to the rate reported in the previous studies from Sudan for E. coli and K. pneumonia (28.9% and 34.8%) [ 16 ], and in agreement with other studies reported the growing prevalence of extended-spectrum beta-lactamase (ESBL) producing isolates from Saudi Arabia ranges from 6% up to 38.5% [ 17 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Carbapenem resistance in A. baumannii complex isolates from hospitalised patients in Germany was 4.4% in 2018, which is significantly lower than those recently observed in hospitals in other regions across the world such as North America (44%) [ 18 ], Latin American (50–90%) [ 18 , 33 , 34 ] and the Asia–Pacific region (79%) [ 18 ]. In China and Saudi Arabia, 71.0% and 60.0% of Acinetobacter isolates from hospitalised patients were found to be carbapenem-resistant, respectively [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several local studies have estimated the rates of susceptibility among gram-positive and gram-negative bacteria in Saudi Arabia [ 6 10 ], but none was comprehensive, and comparisons are complicated by variable methods and study periods that influence the findings explanation and interpretation.…”
Section: Introductionmentioning
confidence: 99%